The Palgrave Handbook of German Idealism
XXIV, 801 p.
Keywords: The Palgrave Handbook of German Idealism features essays from leading scholars on German philosophy. It is the most comprehensive secondary source available, covering not only the full range of work by Kant, Fichte, Schelling and Hegel, but also idealists such as Reinhold and Schopenhauer, critics such as Jacobi, Maimon, and the German Romantics.